2021
DOI: 10.17762/turcomat.v12i3.1022
|View full text |Cite
|
Sign up to set email alerts
|

Librarians Skills and Competencies for Scholarly Communication and Repository Management in Nigeria

Abstract: The rapid change in scholarly communication and knowledge management has transformed the repository services and imposed new skills and competencies for repository management. This study is posed to assess the skills and competencies of librarians for repository management and scholarly communication in academic institutions in Nigeria. The study adopted a survey research design to assess the skills and competencies of the librarians using NASIG “Core Competencies for Scholarly Communication Librarians 2017”. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The librarians need to be aware and competent in these technologies so that they can educate which materials they can upload and share and copyright issues. According to Adam and Kaur (2021), majority of the respondents were familiar with copyright issues is deviating with our study results revealed that only 46% were competent with copyright issues. Electronic conferencing played a significant role during the Covid-19 pandemic and its importance was realized much after the pandemic.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The librarians need to be aware and competent in these technologies so that they can educate which materials they can upload and share and copyright issues. According to Adam and Kaur (2021), majority of the respondents were familiar with copyright issues is deviating with our study results revealed that only 46% were competent with copyright issues. Electronic conferencing played a significant role during the Covid-19 pandemic and its importance was realized much after the pandemic.…”
Section: Discussionsupporting
confidence: 48%
“…On the other hand, they have moderate and low competency skills on metadata development, digitization, applying new technologies to library, library website development and the ability to create different file formats. In Nigeria, Adam and Kuar (2021) assessed librarians skills and competencies for scholarly communication and managing the repository found that majority of the respondents understand digital preservation, repository platforms, collect, store and preserve research output of the institutions and develop policies, author’s rights, knowledge on data description and storage and indicators of research impact. In another study conducted in India, Shastri and Chudasma (2022) found that majority of Gujarat State library professionals rated operating skills as above average and excellent for information literacy skills such as Operating System, MS-Office, DBMS, Library Automation, Cataloguing and Metadata, Subject Gateways, Electronic Bulletin Board, Asynchronous library services (FAQ, E-Mail, Webform etc), RFID and Cloud Computing Service.…”
Section: Information and Communication Technology (Ict) Skillsmentioning
confidence: 99%
“…The benefits of IRs are enormous. Authors such as Adam and Kiran (2021a) recognize that the implementation of IRs will solve the issue of visibility and at the same time facilitate the quick dissemination of indigenous knowledge from Africa. IRs will also improve the impact factor and university ranking (Nunda and Elia, 2019; Christian, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%